The evaluation of clinical eficacy of 17β-estradiol vaginal tablets in the atropic vaginitis therapy - Wlaźlak, Edyta; Surkont, Grzegorz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2004)
In the study 245 women with urogynecologic complaints and estrogen deficiency took part. There was evaluated the eficiency and tolerance of therapy. Conclusions. 1. Vaginal therapy with 25 µg 17β-estradiol tablets is efficient in treatment of atrophic vaginitis and dyspareunia in postmenopausal women. 2. Vaginal therapy with 25 µg 17β-estradiol tablets gives improvement in urinary incontinence complaints in women with estrogen deficiency. 3. Therapy is well tolerated by patients. 4. Vaginal therapy with estradiol tablets in aplicator is noticed by most of the patients as more comfortable than other ways of aplications.